Sudanese Medical Doctors’ Perceptions, Expectations, Experiences and Perceived Barriers Towards the Roles of Clinical Pharmacists: A Cross-Sectional Study - Mahmoud MI; Maatoug MM; Jomaa AAAFA; Yousif M (Dove Medical Press, 2022)
Mohammed Ibrahim Mahmoud,1 Maha Mirghani Maatoug,1 Abd Alkareem Ahmed Fadal Allah Jomaa,2 Mirghani Yousif1 1Department of Clinical Pharmacy & Pharmacy Practice, University of Gezira, Wad Medani, Gezira State, Sudan; 2Department of Pharmacology, University of Gezira, Wad Medani, Gezira State, SudanCorrespondence: Mohammed Ibrahim Mahmoud, Department of Clinical Pharmacy & Pharmacy Practice, Faculty of Pharmacy, 6 Jabra Ave, Al Khartoum, 11111, Sudan, Tel +249118208439, Fax +249183526178, Email Mohammedjrt@gmail.comPurpose: Interprofessional collaboration between physicians and clinical pharmacists has been shown to improve patients' outcome by reduce medical errors, costs and patient adherence. Thus, the purpose of this study was to investigate the medical doctors' perceptions, expectations, experiences, and perceived barriers regarding clinical pharmacists in Wad Medani.Methods: A cross-sectional study was conducted at five major hospitals in Wad Medani, between April and June 2021 using a self-administered questionnaire. The questionnaire was distributed among 178 physicians. The questionnaire consists of four sections, in addition to a demographic section. These four sections measure physicians' perceptions, expectations, experience, and perceived barriers.Results: A total of 178 physicians were enrolled in the study. Physicians were comfortable with clinical pharmacists detecting and preventing prescription errors (55.1%); providing patient education (56.3%). Generally, physicians had high expectations with agreement rate of all the items ranged from 51.7% to 85.4%. Most physicians (79.8%) agreed that clinical pharmacists were a reliable source of general and clinical drug information. 64.0% and 59.0% of physicians perceive the unclear responsibility of clinical pharmacists and the lack of physicians' experience with clinical pharmacists were barriers that can hinder clinical pharmacists' contributions, respectively.Conclusion: Physicians had positive perceptions, expectations, and experiences with clinical pharmacists, and pointed out some barriers clinical pharmacists face. It was suggested that hospitals should recruit more clinical pharmacists to cover each unit within the hospital with clear job description and provide them CPD.Keywords: physicians, clinical pharmacists, perceptions, expectations, experiences, barriers